2022
DOI: 10.48550/arxiv.2202.06074
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The DESI $N$-body Simulation Project -- II. Suppressing sample variance with fast simulations

Zhejie Ding,
Chia-Hsun Chuang,
Yu Yu
et al.

Abstract: Dark Energy Spectroscopic Instrument (DESI) will construct a large and precise 3D map of our Universe. The survey effective volume reaches ∼ 20 Gpc 3 ℎ −3 . It is a great challenge to prepare high-resolution simulations with a much larger volume for validating the DESI analysis pipelines. AbacusSummit is a suite of high-resolution dark-matter-only simulations designed for this purpose, with 200 Gpc 3 ℎ −3 (10 times DESI volume) for the base cosmology. However, further efforts need to be done to provide more pr… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 29 publications
(38 reference statements)
0
5
0
Order By: Relevance
“…Again, the results are found very similar for the 𝑓 NL = 0 and the 𝑓 NL = 100 cases. The Fixed shows a scale-dependent variance reduction similar to Chuang et al (2019), (Ding et al 2022) or (Maion et al 2022), which we fit here with a smooth step function (Equation 13) that we use for the rest of the paper. When adding the Pairing to the Normal simulations, we actually obtain an increment on the variance at large scales in line with Chuang et al (2019), which goes in opposite direction to the original motivation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Again, the results are found very similar for the 𝑓 NL = 0 and the 𝑓 NL = 100 cases. The Fixed shows a scale-dependent variance reduction similar to Chuang et al (2019), (Ding et al 2022) or (Maion et al 2022), which we fit here with a smooth step function (Equation 13) that we use for the rest of the paper. When adding the Pairing to the Normal simulations, we actually obtain an increment on the variance at large scales in line with Chuang et al (2019), which goes in opposite direction to the original motivation.…”
Section: Discussionmentioning
confidence: 99%
“…This is mentioned in several works like Smith & Angulo (2019), however, the correlation coefficient was not explicitly applied to reduce the uncertainty in the analysis. The correlation between Matched-ICs of simulations has been explicitly used in the CARPool method (Chartier et al 2021;Ding et al 2022) but, in that case, between highfidelity mocks and approximate mocks, in order to retrieve unbiased precise clustering statistics from the approximate mocks. Here, we propose a framework to explicitly use the correlation between simulations with Matched-ICs across different cosmologies to reduce the expected variance of the summary statistic and to constrain models to an increased accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, we believe that the procedure outlined in this paper could be applied to augment analytical approximations to 𝑁-body simulations (like L-PICOLA, Howlett et al 2015, or FastPM, Feng et al 2016, as well as semi-analytical models of galaxies, which, in the same vein as lognormal random fields, provide a fast approximation to hydrodynamical simulations by modelling complicated baryonic processes (White & Frenk 1991;Kauffmann et al 1993;Cole et al 1994;Somerville & Primack 1999;Lacey 2001). We further plan to explore the possibility to employ the dataset described in this work to reduce the variance in the statistics of large-scale structure observables using a small number of expensive simulations Ding et al 2022), as well as to replace our WGAN-GP model with either a possibly more stable GAN version (Kwon et al 2021), or with a more compact model, like the one proposed in the context of Lagrangian deep learning (LDL, Dai & Seljak 2021), using graph neural networks (GNNs, see e.g. Zhou et al 2018 for a review) or through normalising flows (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The key idea is to combine a small number of costly simulations with a large number of correlated surrogates. Very recently, Ding et al (2022) tested the CARPool principle to estimate the mean of the two-point and three-point clustering statistics of halos, in order to prepare the high-resolution simulations needed for the Dark Energy spectroscopic Instrument (DESI). By pairing AbacusSummit suite (Maksimova et al 2021) simulations with FastPM approxima-tions, they found ≈ 100 times smaller variances with CARPool at scales 𝑘 ≤ 0.3 ℎMpc −1 than with high-resolution simulations alone.…”
Section: Introductionmentioning
confidence: 99%